Sense of meaning and purpose in life and risk of incident dementia: New data and meta-analysis. (February 2023) - Sutin, Dr. Angelina R; Luchetti, Martina; Aschwanden, Damaris; Stephan, Yannick; Sesker, Amanda A.; Terracciano, Antonio
Abstract: Purpose : A greater sense of meaning and purpose in life is associated with lower dementia risk. The present research examines meaning and incident dementia in the largest sample to date, the UK Biobank, and combines the findings with the published literature on meaning/purpose and dementia risk in a meta-analysis. Method : Participants from the UK Biobank reported on their meaning in life in the 2016/2017 mental health assessment ( N =153, 445). All-cause and cause-specific dementia were derived from hospital and death records through November 2021. Cox regression was used to test the association between meaning in life and risk of incident dementia. Results from the UK Biobank were combined with published studies identified through a systematic literature review in a random-effect meta-analysis (k=8; total N =214, 270). Results : UK Biobank participants were followed up to five years after their assessment of meaning in life; 551 participants developed dementia. For every one-point higher feeling of meaning, there was a 35% decreased risk of all-cause dementia (HR=.74, 95% CI=.67-.82, p <.001). The association was similar controlling for clinical and behavioral risk factors and was not moderated by age, sex, education, or APOE risk status. Similar associations were found for Alzheimer's disease and vascular dementia. The meta-analysis supported the protective association between meaning/purpose and lower dementia risk (HR=.76, 95% CI=.72-.79, p <.001). Conclusions : The present research supports the growing literature that meaning and purpose in life have a robust association with lower risk of developing dementia. Meaning/purpose is a promising intervention target for healthier cognitive outcomes in older adulthood. Highlights: Meaning and purpose in life are associated with lower dementia risk. A similar association was found in the UK Biobank. A meta-analysis with the published literature supported this association. There was no statistical difference between meaning and purpose on dementia risk.